2015
DOI: 10.1038/srep17989
|View full text |Cite
|
Sign up to set email alerts
|

A method for reproducible measurements of serum BDNF: comparison of the performance of six commercial assays

Abstract: Brain-Derived Neurotrophic Factor (BDNF) has attracted increasing interest as potential biomarker to support the diagnosis or monitor the efficacy of therapies in brain disorders. Circulating BDNF can be measured in serum, plasma or whole blood. However, the use of BDNF as biomarker is limited by the poor reproducibility of results, likely due to the variety of methods used for sample collection and BDNF analysis. To overcome these limitations, using sera from 40 healthy adults, we compared the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(181 citation statements)
references
References 60 publications
(99 reference statements)
5
162
1
Order By: Relevance
“…Similarly, the ELISA kits used to measure BDNF have different performance in terms of detection range, sensitivity, and inter-assay variations [62]. In the studies included in our meta-analysis, all the authors correctly specified the producers; however, it cannot be excluded that inter-kit variability plays an important role in BDNF measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the ELISA kits used to measure BDNF have different performance in terms of detection range, sensitivity, and inter-assay variations [62]. In the studies included in our meta-analysis, all the authors correctly specified the producers; however, it cannot be excluded that inter-kit variability plays an important role in BDNF measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The only published reports that we could find with such claims presented no supporting data (Chen et al, 2006; Yoshida et al, 2012). Further, a recent report concerning claims of selectivity used dot blotting, instead of an ELISA approach, for the evaluation (Polacchini et al, 2015). For these reasons, we tested the ability of the BDNF Emax ImmunoAssay kit (Promega) to detect proBDNF and mature BDNF using purified human proBDNF and mature BDNF, and, under identical assay conditions, we found that only mature BDNF was being detected.…”
Section: Discussionmentioning
confidence: 99%
“…The manufacturer of the ELISA kit we use claims 13% cross-reactivity for recombinant human pro-BDNF. The Elisa kit we used has a very low cross-reactivity for proBDNF compared to the other available ELISA kits (see Polacchini et al [55] and Lim et al [56]),…”
Section: Methodsmentioning
confidence: 99%